Abundance, diversity and composition of understory plants along the altitudinal gradient and dominant overstory composition types in the temperate Himalayan region - Sangry, Saveena; Kumar, Praveen; Bhardwaj, D.R.; Dogra, K.S.; Poonam, (Frontiers in Forests and Global Change, 2024)
Introduction The Indian Himalayan forests are remarkable landforms experiencing tremendous climatic variation, constituting complex and diversified ecosystems with prominent vegetation zones. Despite their global significance and substantial research efforts focused on plant diversity in the temperate Himalayan region, only a few studies have explicitly assessed the distribution patterns of understory vegetation in relation to forest compositional types along altitudinal gradients. Methods To cover a wide range of altitudes and diverse overstory compositions, stands were sampled across four altitudinal ranges from 1500 to 3500 meters above mean sea level with increments of 500 meters in elevation steps. The overstory compositions were classified on the basis of dominant tree species in each stand on the similar sites. Vegetation in the shrub and ground layers was surveyed by visually estimating the percentage coverage within circular plots. Results A total of 99 understory species including 37 species each in the shrub layer, 62 species in the herb layer vegetation were recorded. The abundance, species diversity and composition of understory vegetation differed significantly along the altitudinal gradient and dominant overstory composition types. Moreover, distinct understory vegetation communities were observed at lower elevations compared to higher elevations, with middle elevations exhibiting intermediate vegetation characteristics. The study also highlighted the importance of dominant overstory composition types in shaping the pattern of understory vegetation abundance, species diversity and composition in the temperate Himalayan region. The higher resource conditions associated with broadleaved stands supported higher understory species abundance at lower elevations, while the heterogeneous conditions induced by the mixedwood stands promoted higher understory species diversity. Conclusion The hump shaped pattern along the altitudinal gradient appeared to be the most dominant pattern of plant abundance and species diversity and call for more conservation concern towards the middle elevation zones in the temperate Himalayan region. Furthermore, the management interventions should aim at maintaining diverse range of overstory composition types for conserving biodiversity and their ecological functions in the temperate Himalayan region.